TEACHING PRACTICUM OF PRE-SERVICE TEACHERS IN EFL CLASSROOMS: QUESTIONING TYPES AND PURPOSES - Milma Vinca Cantikka Hidayat; Siti Nurjanah; Elis Homsini Maolida (Siliwangi University, 2020)
In order to potentially support the students to master the language, the teachers can give questions to stimulate them. This study explores types of questions used by three pre-service teachers and their frequency as well as the teachers’ purposes by looking at the contexts in which they used the questions. Theory of Cotton (1988) was used to analyse the data which categorized questions into three major types namely yes/no questions, open closed question, and display referential question. Employing descriptive qualitative approach, the data were taken from video transcriptions that were analysed and categorized into their question category. The participants were three pre-service teachers who practiced in three different senior high schools. The result showed that the total of 128 data consists of 14 opened referential questions, 81 questions belonged to closed display questions, and 33 data belonged to yes/no questions. Therefore, it can be concluded that the most frequently used type of question is closed display questions. From the result of observation focusing on the contexts and situations when the teachers gave the questions, it was revealed that the purposes of the open and referential questions were more to stimulate students in stating information and pursuing knowledge on their own and ask students’ opinion, reason, or judgement. Whereas, the purposes of closed and display questions were likely to make the students focused and to check students’ knowledge and understanding. Lastly, the yes/no questions’ purposes were making the students focus and attracting students’ activeness.